Knowledge about management of avulsed tooth among primary school teachers of Riyadh - Md Ali Salem Abuelqomsan; Zaid Abdulaziz Aljeaidi; Adel Obaid Albalawi; Ibrahim Abdullah Abalkhayl; Inderjit Murugendrappa Gowdar (Wolters Kluwer Medknow Publications, 2017)
Background: Traumatic injuries are common among the school children during physical activity. As teachers being the first persons to come in contact, it is essential that they know to manage such situations. Hence, the aim of this study was to evaluate the knowledge level of a group of Saudi primary school teachers in the management of avulsed tooth. Methodology: The study was conducted among 300 male teachers and schools, who were randomly selected from Riyadh city. Results: The results showed that 68.3% had a previous experience about avulsed tooth in children. 36.3% (109 teachers) only had first aid training of dental trauma. Nearly, 61.7% knew about replant re-implantation of the avulsed tooth and regarding the storage media only 3.3% had chosen childrens' mouth/ saliva as a suitable media. Conclusion: This study shows a lack of knowledge regarding tooth avulsion and its emergency management among teachers in Riyadh city. Therefore, educational programmers are necessary to improve their level of knowledge.